Novel acetogenins from the leaves of Dasymaschalon sootepense - Andrea Sinz (2018)
The hexane extract from the leaves of Dasymaschalon sootepense Craib (Annonaceae) showed strong cytotoxic activity against the L1210 tumor cell line. Activity-directed fractionation of the extract by column chromatography on silica gel and high-pressure liquid chromatography led to the isolation of the acetogenins 1-4 as the main active principles. The structures of the two novel structures named sootepensin A (1) and sootepensin B (2) were elucidated by spectroscopic analysis (UV, EI- and ESI-MS, 1D- and 2D-1H- and 13C-NMR). The absolute configurations were established by 2D-NMR experiments utilizing Mosher esters. Two recently described compounds, tonkinin C(3) and tonkinesin C(4), were also isolated and are new to the genus Dasymaschalon. All four acetogenins were found to be highly cytotoxic against the L1210 tumor cell line.